Cardiovascular risk management in antiphospholipid syndrome: trends over time and comparison with rheumatoid arthritis and diabetes mellitus - Eleana Bolla; Nikolas Tentolouris (Lupus Science and Medicine)
Objective Antiphospholipid syndrome (APS) is characterised by increased cardiovascular morbidity and mortality, related to thrombo-inflammatory and atherogenic mechanisms. We examined the achievement of traditional cardiovascular risk factor (CVRF) therapeutic goals in APS versus other high cardiovascular risk disorders such as rheumatoid arthritis (RA) and diabetes mellitus (DM), and trends over time.Methods 122 patients with APS (74 primary APS, female 68%, mean age 44.5±11.3) were classified according to their first visit (2011–2015 and 2016–2020 APS subgroups, 61 patients in each subgroup) and matched 1:1 for age/sex with patients with RA and DM. Cardiovascular risk was estimated by the Systemic Coronary Risk Evaluation, and the CVRF therapeutic targets were defined according to the European Society of Cardiology (ESC) guidelines. Individual and multiple CVRF control was compared between APS subgroups, and in APS versus RA and DM.Results We found a comparable or higher prevalence of CVRFs between APS and age-matched/sex-matched patients with RA and DM but low CVRF target attainment in APS according to the ESC guidelines. Despite improving trends between 2011–2015 and 2016–2020, CVRF control in high/very high-risk patients with APS was 12%, 18%, 24% and 35% for low-density lipoprotein, waist circumference, exercise and body mass index, respectively, and 59%–65% for triglycerides, high-density lipoprotein (HDL) and blood pressure, in 2016–2020 subgroup. CVRF control was worse in APS versus RA for smoking (p=0.014), HDL (p<0.001), waist circumference (p=0.042) and five CVRFs (p=0.030), and versus DM for exercise (p=0.077). Similar results were found in the sensitivity analysis.Conclusions Comparable prevalence of modifiable CVRFs to RA and DM but suboptimal CVRF target achievement was observed in APS, especially in high/very high-risk patients, highlighting the need for CVRF management strategies.